2021
DOI: 10.1371/journal.pone.0260772
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blockers and oral squamous cell carcinoma survival: A propensity-score-matched cohort study

Abstract: Objectives Angiotensin II receptor blockers (ARBs) improve the survival rates of patients with various cancers. However, it remains unclear whether ARBs confer a survival benefit on patients with oral squamous cell carcinoma (OSCC). Here, we assessed the associations between ARB use and survival in patients with OSCC of different stages. Materials and methods This was a 10-year retrospective cohort study of OSCC patients. We enrolled 7,558 patients diagnosed with oral cancer between January 2007 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The authors also demonstrated that Ang-(1-7) might reduce tumor growth in NPC xenografts by downregulating the PI3K/Akt/mTOR signaling pathway. Another group assessed the association between the use of AT1 receptor blockers (ARBs) and the survival rates in patients with oral SCC of different stages, showing increased overall survival (OS) rate of ARB users after 180 days of treatment [ 32 ]. Although this suggested an important therapeutic role of Ang-(1-7), since ARBs increase the concentration of the heptapeptide, the effects of Ang-(1-7) in the oral cavity have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated that Ang-(1-7) might reduce tumor growth in NPC xenografts by downregulating the PI3K/Akt/mTOR signaling pathway. Another group assessed the association between the use of AT1 receptor blockers (ARBs) and the survival rates in patients with oral SCC of different stages, showing increased overall survival (OS) rate of ARB users after 180 days of treatment [ 32 ]. Although this suggested an important therapeutic role of Ang-(1-7), since ARBs increase the concentration of the heptapeptide, the effects of Ang-(1-7) in the oral cavity have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that OSCC patients have a significantly higher comorbidity burden at diagnosis and that survival outcomes are significantly decreased with the presence of additional comorbidities ( 2 , 15 , 16 ). Several hypotheses concerning the underlying biological mechanisms have been suggested for the reduced survival in patients with malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…We determined comorbidity status using the criteria of at least 1 instance of coding during hospitalization or at least 3 instances during outpatient visits, as established in previous studies. 13,14 We also collected preoperative laboratory data, such as lymphocyte count, serum albumin, and hemoglobin level. This data was obtained from a blood draw within thirty days before the operation.…”
Section: Definition Of Variables and Study Designmentioning
confidence: 99%